Analysis of Optimal Power Flow using Hybrid Fruitfly Algorithm (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
In this paper, hybrid fruit fly algorithm is proposed to find the optimal solution for optimal power flow (OPF) problem in a power system. The proposed approach is applied to determine the optimal settings of control variables of the OPF problem. The performance of the proposed approach examined and tested on the himmelblau test function and 30-bus test systems with different objective functions and is compared to other heuristic methods reported in the literature recently. Simulation results obtained from the proposed approach indicates that HFFA provides effective and robust high-quality solution for the OPF problem.